Structures of the human cholecystokinin 1 (CCK1) receptor bound to Gs and Gq mimetic proteins provide insight into mechanisms of G protein selectivity - Mobbs, Jesse I.; Belousoff, Matthew J.; Harikumar, Kaleeckal G.; Piper, Sarah J.; Xu, Xiaomeng; Furness, Sebastian G. B.; Venugopal, Hari; Christopoulos, Arthur; Danev, Radostin; Wootten, Denise; Thal, David M.; Miller, Laurence J.; et al. (PLOS Biology, 2021)
Cryo-EM structures of the G protein-coupled receptor CCK1R bound to the CCK peptide agonist CCK-8 and two distinct transducer proteins – its primary transducer Gq, and the more weakly coupled Gs – reveal unexpected modes of G protein interaction.